Аннa Андріївнa Іващенко: до 80-ти річчя науковиці - Перегрим, М.М.; Димитрова, Л.В.; Абідкулова, К.Т.; Мойсієнко, І.І. (CHORNOMORSKI BOTANICAL JOURNAL, 2021)
Аннa Андріївнa Іващенко: до 80-ти річчя науковиці